Implikatur dan Daya Pragmatik di Balik Ungkapan Motivasi Berorganisasi Kalangan Peserta Didik Berlatar Belakang Budaya Jawa - Khasanah, Eva Nur, Prof. Dr. Harun Joko Prayitno, M.Hum (2016)
Study has three objectives. a) Describe the form mplicature behind the motivational phrase organizational among learners. b) Identifying the implicature aim and intent contained behind of motivational phrase organizational among leaners. c) Describe the form and intent contained behind force of pragmatica organizational motivational phrase among leaners. This study method is descriptive qualitative. Collecting data in this study using techniques see and record. The data has been analyzed using methods match those techniques appeal equalize circuit ( HBS ) and circuit techniques to discern appeal ( HBB ) .The results of this study is, a) there are two forms behind the phrase of motivation among learners, is conventional implicature representative and conventional implicatures commissive. b)Implicature intention behind the phrase of motivation among learners there are four, namely informing, expressed a desire, expressed a hope, and expressed confodence. Interest implicature found varied, depending on each speech that Pn. c) Form of pragmatics force is expressed using literal indirect speech acts. The intent of the pragmatics force there are three, is force of ask, force to influence, force of critize, and force of praise.